Principal instructional leadership practice and its relationship with teacher job performance - Yuanyuan, Xiang; Alias, Bity Salwana (International Journal of Evaluation and Research in Education (IJERE), 2025)
Excellent principal leadership actions will be guidance for teachers’ high-quality teaching performance. However, the role of instructional principal is not fully utilized, and principals lack the highly effective leadership qualities necessary to promote teachers in improving teacher job performance. This study was conducted in Shenzhen, China to investigate the effect of principal instructional leadership practices on teachers’ job performance. This study employed a quantitative approach. The sample of the study was all private secondary school teachers in Shenzhen China, consisting of 297 teachers selected from 1,300 populations. To figure out the research questions, SPSS software was used with the help of descriptive and inferential analysis. The findings of this study show that both principal instructional leadership practice and teachers’ job performance are at a high level. Moreover, there was a very strong positive relationship between two variables (r=0.974). In conclusion, the findings underscore the significance of principals’ instructional leadership attributes on teacher job performance and provide implications for the government and the school principals regarding the implementation of principal training system or the improvement of educational management policy in private schools throughout Shenzhen, China.